Consensus organizing building communities of mutual self-interest - Eichler, Mike.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2007)
Written in a logical, teachable, and pragmatic style,this book provides a model of social change for the 21st century. Through real examples, the author illustrates how anyone can practice consensus organizing and help the poor, forgotten, and disempowered.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Community organization -- United States; Social action -- United States; Consensus (Social sciences) -- United States; Community development -- United States; Electronic books